The socially constructed and reproduced youth delinquency in Southeast Asia : advancing positive youth involvement in sustainable futures - Hung, Jason (Diverse perspectives on creating a fairer society, 2023)
Youth delinquency, involving behaviours such as smoking, drinking, and premature sexual misconduct, is an ongoing issue in Southeast Asia. Though both individual governments and the Association of Southeast Asian Nations (ASEAN) have implemented regulations to minimise the development of youth delinquency, adolescents' involvement in deviant behaviours continues to rise. Analysing the causes and effects of a variety of youth delinquent behaviours, both digital and conventional, The Socially Constructed and Reproduced Youth Delinquency in Southeast Asia aligns insightful sociological inquiry with an ongoing regional phenomenon. Delving into both the individual and the societal costs of such behaviours, Jason Hung considers their impact on SEA countries' pursuit of sustainable futures. With suggestions for sharpening regional competitiveness and habitability across SEA, each chapter also presents informed policy recommendations for coping with the entrenched, complex problems of youth delinquency efficiently and effectively. With emphasis on advancing positive youth involvement for a more robust future, Hung presents a compelling evocation of the role of adolescents in the creation of a fairer society in Southeast Asia.